Laboratory Equipment Type Fiber Optic Refractometer - Turan, J.; Ovsenik, L.; Benca, M.; Carome, E. F. (Radioengineering Society, 2002)
Using fiber optics and micro optics technologies we designed an innovative fiber optic index of refraction transducer that has unique properties. On the base of this transducer a laboratory equipment type fiber optic refractometer was developed for liquid index of refraction measurements. Such refractometer may be used for medical, pharmaceutical, industrial fluid, petrochemical, plastic, food, and beverage industry applications. For example, it may be used for measuring the concentrations of aqueous solutions: as the concentration or density of a solute increase, the refractive index increases proportionately. The paper describes development work related to design of laboratory type fiber optic refractometer and describes experiments to evaluation of its basic properties.
Keywords: Refractometers; index of refraction measurement; fiber optic index of refraction transducer